Cost effectiveness of radial access for diagnostic cardiac catheterization and coronary intervention. Issue 4 (25th March 2013) - Applegate, Robert; Sacrinty, Matthew; Schafer, Pascha; Smith, Justin; Gandhi, Sanjay; Kutcher, Michael; Santos, Renato; Cecile, Adam; Little, William
<x xml:space="preserve">Abstract</x> Objectives To evaluate the cost effectiveness of diagnostic cardiac catheterizations (CATH) and coronary interventions (PCI) performed using radial artery (RA) access compared to femoral artery (FA) access. Background CATH and PCI performed from the RA reduce access site complications compared to FA, but can increase procedure duration, and equipment and contrast use. Whether resulting increases in utilization costs are offset by reduced costs of complications is uncertain. Methods In all, 6, 726 CATH and PCI (RA, 3, 368; FA, 3, 358) were performed from January 2009 to December 2011. Procedural costs and cost of access site complications were compared for propensity‐matched CATH (RA and FA, 1, 222) and PCI (RA and FA, 570) throughout a complete transition of the lab from a preferred FA to preferred RA strategy. Results Adjusted mean total costs were $10 more (95% confidence interval $613 less to $610 more) for RA‐CATH versus FA‐CATH and $732 less ($1, 345 less to $156 less) for RA‐PCI versus FA‐PCI. The incremental cost per vascular or bleeding complication avoided with RA‐CATH was $1, 265, whereas RA was economically dominant with lower costs and fewer complications compared to FA for PCI and all procedures. Conclusions Radial access for CATH and PCI reduced access site complications and overall costs compared to FA procedures with similar baseline clinical and procedural characteristics, making it an economically advantageous strategy. © 2012 Wiley Periodicals, Inc.